A reconstruction of objets by interferometric profilometry with positioning system of labeled target periodic (2015)
A method to extract 3D information using a white light interferometer without using PZT is presented. Instead a positioning system that uses the phase sensitivity of a target periodic is employed. The image treatment realized on the periodic target permits to calculate the relative distance between Mirau objective and object surface. Topographic reconstructions of objects with dimensions of some tenths of millimeters were calculated with an accuracy of approximately 28 nanometers. Theoretical analysis and experimental results are shown.